2012
DOI: 10.1016/j.jcf.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibiotic susceptibility patterns in Pseudomonas aeruginosa isolated from adult patients with cystic fibrosis (CF) with invasive Pseudomonas aeruginosa from non-CF patients

Abstract: The role of bacterial pathogens in CF pulmonary disease contributes greatly to the morbidity and mortality in patients with CF. CF patients have recurrent and chronic respiratory tract infections and most of their morbidity and mortality is due to such infections throughout their life [1,2]. These infections are usually dominated by non-fermenting Gram-negative organisms (Burkholderia cenocepacia and Stenotrophomonas maltophilia), including Pseudomonas aeruginosa. P. aeruginosa is the single most important pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
(10 reference statements)
0
8
1
Order By: Relevance
“…Similar results were also obtained in another Turkish multi-center study comparing the antibiotic resistance of P.aeruginosa isolates from sputum samples of patients with CF and lower respiratory tract samples of patients without CF (24). In contrary to this Rao et al showed that isolates from blood samples of CF patients were more resistant to antibiotics than those of non-CF patients (25). It may be because of several classes of antibiotics used in the management of CF airways infection.…”
Section: Discussionmentioning
confidence: 91%
“…Similar results were also obtained in another Turkish multi-center study comparing the antibiotic resistance of P.aeruginosa isolates from sputum samples of patients with CF and lower respiratory tract samples of patients without CF (24). In contrary to this Rao et al showed that isolates from blood samples of CF patients were more resistant to antibiotics than those of non-CF patients (25). It may be because of several classes of antibiotics used in the management of CF airways infection.…”
Section: Discussionmentioning
confidence: 91%
“… 24 Because the relevance of organism antibiotic sensitivity patterns has been questioned in recent years, the use of two antibiotics with different mechanisms of action to improve outcome is still common practice in most CF centres. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance is a significant and increasing problem in medical practice and a common clinical complication in CF patients infected with P aeruginosa , which tends to present more resistance than P aeruginosa from non‐CF patients to all clinically relevant classes of antibiotics …”
Section: Introductionmentioning
confidence: 99%
“…This fact seems to reflect the chronic burden of antibiotic exposure usually present in CF treatment …”
Section: Introductionmentioning
confidence: 99%